Implementasi Penyelesain Sengketa Informasi Publik pada Komisi Informasi Provinsi Jambi - Herma Yanti (Universitas Batanghari Jambi, 2022)
The existence of the Jambi Provincial Information Commission is expected to be able to resolve public information disputes effectively and efficiently so that the information disclosure mandated by Law Number 14 of 2008 concerning Public Information Disclosure can be realized. However, as an institution that was newly formed in 2014, of course, it cannot be separated from various limitations that affect the implementation of the Information Commission's functions. Therefore, this study aims to further examine how the implementation of public information dispute resolution at the Information Commission in Jambi Province. According to this purpose, this research is an empirical legal research with a socio legal research approach. The data used in this study are dispute resolutions carried out for the last 3 (three) years from 2019 to 2021. These data were collected through interviews with members of the Information Commission who were related and who understood the problem under study and conducted studies on various documents relevant. From the results of the study, it is known that the Jambi Information Commission has carried out the resolution of the information dispute as determined, but in its implementation it can be said that it has not been carried out effectively and efficiently, because only a small part can be resolved quickly through mediation, most of the others must be resolved further through the process. non-litigation adjudication which consists of several stages so it requires more time. In addition, because not all decisions handed down by the Commission can be accepted by the disputing parties, they will proceed to court.